The southern front history and politics in the cultural war - Genovese, Eugene D. 1930-2012 (Univ. of Missouri Press, 1995)
In "The Question," a searing essay that has already provoked heated debate, Genovese argues that a commitment to presumed "larger goals" led the radical Left to ignore, and therefore become complicit in, the mass murders of communism. And he suggests that today a similar blindness is fostering the promotion of totalitarian measures on our campuses. "We are today indeed engaged in a cultural war," writes Genovese. "To win that war will require a new and hitherto unimaginable coalition across political and racial lines.